2015
DOI: 10.1590/s1980-65742015000100005
|View full text |Cite
|
Sign up to set email alerts
|

Space protection dynamics in basketball: Validation and application to the evaluation of offense-defense patterns

Abstract: Abstract-The aims of this study were twofold: i) to validate classes of defensive actions (i.e., space protection dynamics -SPDs) for containing offense in basketball; and ii) to propose a novel approach to analyze matches based on the interaction of a space creation dynamic (SCD) and a respective SPD. Kappa statistics revealed high intra-and inter-raters values, supporting the reliability of the defined SPDs. Six matches of the Spanish professional basketball finals were analyzed to achieve the second purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 17 publications
1
15
0
2
Order By: Relevance
“…Set offence was by far the most prevalence game phase studied, probably because more than eight out of ten total match possessions are played during a structured game. To increase scoring options, authors highlight the importance of 1vs1 situations, screens, ball circulation (pass and reception), and space creation dynamics during the set offence (Courel, Suárez, Ortega, Piñar, & Cárdenas, 2013;Gómez et al, 2015;Lamas, De Rose Junior, et al, 2011;Muñoz, Serna, Daza, & Hileno, 2015;Santana et al, 2015). Additionally, some authors have explored set defense, finding that man-on-man was the most used style, but half-court zone resulted more effective.…”
Section: Game Phase and Players' Rolementioning
confidence: 99%
See 2 more Smart Citations
“…Set offence was by far the most prevalence game phase studied, probably because more than eight out of ten total match possessions are played during a structured game. To increase scoring options, authors highlight the importance of 1vs1 situations, screens, ball circulation (pass and reception), and space creation dynamics during the set offence (Courel, Suárez, Ortega, Piñar, & Cárdenas, 2013;Gómez et al, 2015;Lamas, De Rose Junior, et al, 2011;Muñoz, Serna, Daza, & Hileno, 2015;Santana et al, 2015). Additionally, some authors have explored set defense, finding that man-on-man was the most used style, but half-court zone resulted more effective.…”
Section: Game Phase and Players' Rolementioning
confidence: 99%
“…Moreover, players' role analysis has been chiefly focused on the player with the ball. However, most recent studies showed interest in exploring specific attacker and defender roles, particularly when performing on ball screens and using space creation dynamics (Gómez et al, 2015;Santana et al, 2015).…”
Section: Game Phase and Players' Rolementioning
confidence: 99%
See 1 more Smart Citation
“…Players' dynamics are determined by specific offensive aims such as to create free space to pass and shoot, enhance effective scoring options and minimize defensive pressure (Remmert, 2003). Through the categorization of player interactions in matches, research studies have identified a variety of actions used in the offence to create (1 vs. 1, screens on and off the ball, cuts towards the basket) and protect (defensive help, switch, screen deny) space (Lamas, et al, 2011;Santana, et al, 2015). These techniques have been implemented to analyse and model offensive and defensive interactions in elite teams (Lamas, Santana, Heiner, Ugrinowitsch, & Fellingham, 2015;Lorenzo Calvo, García, & Navandar, 2017;Vaquera, García-Tormo, Gómez Ruano, & Morante, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A defesa foi classificada em: (i) Individual e (ii) Zonal. Para fazer a análise do comportamento tático foram utilizadas as DPE (Dinâmica de Proteção de Espaço) (10) , definidas como comportamentos defensivos que tem como objetivo uma ocupação do espaço de maneira a impedir que uma finalização ocorra e ensejando a recuperação da posse da bola. Existe uma relação de uma DCE (Dinâmica de Criação de Espaço) (6) para muitas possibilidades das correspondentes DPE 7,8 .…”
Section: Introductionunclassified